Improving the room-temperature ferromagnetism in ZnO and low-doped ZnO:Ag films using GLAD sputtering - Correa, Marcio A. (2021)
ZnO and doped ZnO films with non-ferromagnetic metal have been widely used as biosensor elements. In these studies, the electrochemical measurements are explored, though the electrical impedance of the system. In this sense, the ferromagnetic properties of the material can be used for multifunctionalization of the sensor element using external magnetic fields during the measurements. Within this context, we investigate the room-temperature ferromagnetism in pure ZnO and Ag-doped ZnO films presenting zigzag-like columnar geometry. Specifically, we focus on the films’ structural and quasi-static magnetic properties and disclose that they evolve with the doping of low-Ag concentrations and the columnar geometry employed during the deposition. The magnetic characterization reveals ferromagnetic behavior at room temperature for all studied samples, including the pure ZnO one. By considering computational simulations, we address the origin of ferromagnetism in ZnO and Ag-doped ZnO and interpret our results in terms of the Zn vacancy dynamics, its substitution by an Ag atom in the site, and the influence of the columnar geometry on the magnetic properties of the films. Our findings bring to light an exciting way to induce/explore the room-temperature ferromagnetism of a non-ferromagnetic metal-doped semiconductor as a promising candidate for biosensor applications.